Deadweight loss and taxation of earned income: Evidence from tax records of the UK self-employed - Laura Blow; Ian Preston (Institute for Fiscal Studies (IFS), 2002)
Responses to changes in marginal income tax rates can be more complex than a simple adjustment in hours worked. Given this, a more inclusive way to assess the deadweight costs of taxes on labour income is to examine the effect of changes in the marginal tax rate on taxable income rather than on labour supply. In this paper we apply a grouping estimator to data from the UK Survey of Personal Incomes so assess the magnitude of taxable income responses of the self employed. Our results point to a modest degree of deadweight loss.
Keywords: 330